Efficacy of a sheet pile wall as a wave barrier for railway induced ground vibration. Issue 84 (May 2016) - Dijckmans, A.; Ekblad, A.; Smekal, A.; Degrande, G.; Lombaert, G.
Abstract: This paper investigates the effectiveness of a sheet pile wall to reduce railway induced vibration transmission by means of field measurements and numerical simulations. At Furet, Sweden, a sheet pile wall has been installed in the soil near the track to reduce train induced vibrations in houses close to the track. The depth of the sheet piles is 12 m with every fourth pile extended to 18 m . The efficacy of the wall is determined from in situ measurements of free field vibrations during train passages before and after installation of the sheet pile wall. The field test shows that the sheet pile wall reduces vibrations from 4 Hz upwards. Up till 16–20 Hz, the performance generally increases with frequency and typically decreases with increasing distance behind the wall. The performance is further studied by means of two-and-a-half-dimensional coupled finite element–boundary element models. The sheet pile wall is modelled as an orthotropic plate using finite elements, while the soil is modelled as a layered halfspace using boundary elements. The sheet pile wall acts as a stiff wave barrier and the efficacy is determined by the depth and the stiffness contrast with soil. The reduction of vibration levels is entirely due to the relatively high axial stiffness and plate bending stiffness with respect to the horizontal axis of the sheet pile wall; the plate bending stiffness with respect to the vertical axis is too low to affect the transmission of vibrations. Therefore, it is important to take into account the orthotropic behaviour of the sheet pile wall. It is concluded that a sheet pile wall can effectively act as a wave barrier in soft soil conditions provided that the wall is sufficiently deep. Abstract : Highlights: A 100 m long barrier has been built in the soil along a railway track in Sweden. The barrier consists of 12 m deep sheet piles with every fourth pile extended to 18 m. The wall is effective and results in vibration reduction from 4 Hz upwards. A good agreement between experiments and numerical predictions is found at short distances behind the wall. The orthotropic behaviour of the wall must be accounted for in simulations.